TINJAUAN ISLAMIC SERVANT-LEADERSHIP PADA SISTEM KEPEMIMPINAN PEMPROV DKI JAKARTA DALAM MENANGANI PANDEMI COVID-19 - Firsty Izzata Bella (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: This study aims to deepen the treasures of Islam and explore the history of Islam in its heyday in terms of leadership and to review how the concept of Islamic Servant-Leadership is implemented as a leadership style by the DKI Jakarta Provincial Government in dealing with Covid-19. The qualitative-descriptive research method is used through content analysis to organize and derive meaning from the data collected and to draw realistic conclusions. By using the ten characteristics of Islamic Servant Leadership, it was found that the leadership practiced by the Provincial Government of DKI Jakarta has met the qualifications to be declared a Servant-Leader or implement Servant-Leadership while handling the Covid-19 pandemicKeywords: Islamic Servant Leadership, Leadership, Covid-19, Provincial Government